Surface‐Dependent Electrocatalytic Activity of CoSe2 for Lithium Sulfur Battery. Issue 11 (3rd March 2023) - Liu, Xiaobiao; Zheng, Yibing; Zhang, Mengjiao; Qi, Shiyang; Tan, Ming; Zhao, Ruwei; Zhao, Mingwen
Abstract: Electrocatalysts play key roles in improving the performance of lithium sulfur (Li‐S) batteries. Here, the electrocatalytic activity of different CoSe2 surfaces for the polysulfide redox reactions in Li‐S batteries, by means of first‐principle calculations is considered. The authors demonstrate that there are obvious differences in surface energy (0.7–2.34 J m −2 ), adsorption energy for lithium polysulfides (LiPSs) (1.2–3.5 eV), Gibbs free energy of sulfur reduction reaction (SRR) (0.37–1.16 eV), and Li2 S decomposition barrier (0.15–0.94 eV) among different CoSe2 surfaces, and thus lead to the different electrocatalytic activity for different CoSe2 surface. The stoichiometric CoSe2 surface with high surface energy, such as the (001) surface, tends to have stronger adsorption energy and larger SRR Gibbs free energy for LiPSs. The surface electron states are mainly dominated by p – d hybridization orbitals and the p ‐band center is vital for the surface electrocatalytic properties. Such surface‐dependent mechanism may shed light on the design of sulfur host materials for high‐performance Li‐S batteries. Abstract : Density functional theory is a powerful tool for theoretically designing and understanding lithium‐sulfur battery materials on an atomic scale. The different catalytic activities caused by the surface effects are very charming. The surface‐dependent electrocatalytic effect of the sulfur reduction reaction of CoSe2 may shed light on the design of sulfur host materials for high‐performance lithium‐sulfur batteries.